Choroidal Metastatic Carcinoma Accompanied With Sjögren Syndrome Initially Presenting as Acute Glaucoma With Angle Closure: Case Report - Chen, Chunli; Hu, Feng; Cheng, Yizhe; Hu, Zhixiang; Wang, Ge; Peng, Xiaoyan (Frontiers in Ophthalmology, 2022)
Introduction : To report a case of choroidal metastatic carcinoma accompanied with Sjogren syndrome initially presenting as acute glaucoma with angle closure. Case description : A 47-year-old female complaining about swelling pain and blurred vision in the right eye for 3 days. The patient had poor response to regular medications for controlling intraocular pressure, but showed very good response to local corticosteroid eye drops after three days with deepening of anterior chamber and significant decline of intraocular pressure. The patient had a notable previous history of dry eyes, dry mouth, and joint pain. The brain, ocular MRI and lung CT with enhancement showed extrapulmonary and pulmonary lesions, immunological abnormities and symptoms supported the diagnosis of Sjogren syndrome. Conclusion: The ophthalmologist should pay attention to differential diagnosis of angle-closure glaucoma from secondary glaucoma in cases with choroidal-retinal detachment or macular folds, which could be ocular manifestation of choroidal metastatic carcinoma in rare condition.